Advances in Functionally Graded Materials and Structures - Ebrahimi, Farzad (IntechOpen, 2016)
Functionally graded materials (FGMs) were initially designed as thermal barrier materials for aerospace structures and fusion reactors and now they are also considered as potential structural materials for future high-speed spacecraft and recently are being increasingly considered in various applications to maximize strengths and integrities of many engineering structures. This book is a result of contributions of experts from international scientific community working in different aspects of FGMs and structures and reports on the state of the art research and development findings on this topic through original and innovative research studies. Through its six chapters the reader will have access to works related to processing, sintering properties and applications of functionally graded ceramics and new processing routes for FGMs while it introduces some specific applications, such as functionally graded annular fins and the high-performance self-lubricating ceramic composites with laminated graded structure. Besides, it presents an experimental crack propagation analysis of aluminum matrix FGMs and a unified accurate solution for three-dimensional vibration analysis of functionally graded plates and cylindrical shells with general boundary conditions.